Cenozoic Methane-Seep Faunas of the Caribbean Region. - Steffen Kiel; Bent T Hansen (PLoS ONE, 2015)
We report new examples of Cenozoic cold-seep communities from Colombia, Cuba, the Dominican Republic, Trinidad, and Venezuela, and attempt to improve the stratigraphic dating of Cenozoic Caribbean seep communities using strontium isotope stratigraphy. Two seep faunas are distinguished in Barbados: the late Eocene mudstone-hosted 'Joes River fauna' consists mainly of large lucinid bivalves and tall abyssochrysoid gastropods, and the early Miocene carbonate-hosted 'Bath Cliffs fauna' containing the vesicomyid Pleurophopsis, the mytilid Bathymodiolus and small gastropods. Two new Oligocene seep communities from the Sinú River basin in Colombia consist of lucinid bivalves including Elongatolucina, thyasirid and solemyid bivalves, and Pleurophopsis. A new early Miocene seep community from Cuba includes Pleurophopsis and the large lucinid Meganodontia. Strontium isotope stratigraphy suggests an Eocene age for the Cuban Elmira asphalt mine seep community, making it the oldest in the Caribbean region. A new basal Pliocene seep fauna from the Dominican Republic is characterized by the large lucinid Anodontia (Pegophysema). In Trinidad we distinguish two types of seep faunas: the mudstone-hosted Godineau River fauna consisting mainly of lucinid bivalves, and the limestone-hosted Freeman's Bay fauna consisting chiefly of Pleurophopsis, Bathymodiolus, and small gastropods; they are all dated as late Miocene. Four new seep communities of Oligocene to Miocene age are reported from Venezuela. They consist mainly of large globular lucinid bivalves including Meganodontia, and moderately sized vesicomyid bivalves. After the late Miocene many large and typical 'Cenozoic' lucinid genera disappeared from the Caribbean seeps and are today known only from the central Indo-Pacific Ocean. We speculate that the increasingly oligotrophic conditions in the Caribbean Sea after the closure of the Isthmus of Panama in the Pliocene may have been unfavorable for such large lucinids because they are only facultative chemosymbiotic and need to derive a significant proportion of their nutrition from suspended organic matter.